A Complementary Aggregation Induced Emission Pair for Generating White Light and Four‐Colour (RGB and Near‐IR) Cell Imaging. Issue 3 (3rd February 2017) - Sarkar, Samir Kumar; Mukherjee, Sanjoy; Garai, Aditya; Thilagar, Pakkirisamy
Abstract: A straightforward strategy for the generation of white‐light emission in aqueous media is reported. Using a blue‐emissive AIE‐active (aggregation‐induced emission) 1, 8‐naphthalimide‐based sensitizer and a boron‐dipyrromethene‐based red emitter as a dopant, water‐dispersible nanostructures with tuneable emission features are produced. The white‐light emissive (WL) nanoaggregates are stable at neutral pH and have been elegantly utilised for four‐colour cell imaging (including nearinfrared imaging). Abstract : Complementary components : A straightforward strategy for the generation of white‐light emission in aqueous media is reported. A blue‐emissive AIE‐active naphthalimide derivative and a boron‐dipyrromethene‐based red emitter as dopant were used to prepare white‐light‐emissive nanoaggregates which were stable at neutral pH. The system was employed in four‐colour cell imaging (including near infra‐red imaging). AIE=aggregation‐induced emission.